Interdisciplinary research approaches to multilingual education - Aravossitas, Themistoklis; Kourtis-Kazoullis, Vasilia; Skourtou, Eleni; Trifonas, Peter Pericles, 1960- (London ; New York : Routledge, Taylor & Francis Group, 2019)
"Recently intensified global mobility has reinforced the interest for ethnolinguistic diversity and multilingualism in education and society. Interdisciplinary Research Approaches to Multilingual Education brings together current interdisciplinary perspectives in multilingual and second language education to examine research and language teaching in specific countries, as well as different aspects of multilingual education that include language policies and ICT applications"--
Linguistic rights and educational policies: aspects of minority language education in Europe / Giorgos Mavrommatis, Syrmo Kapoutsi, and Anastasia Karagianni -- Building a multilingual learning community : educational partnerships with parents in a multilingual preschool in Iceland / Hanna Ragnarsodottir -- Case study research on the less known multilingual educational program of Val d'Aran in Catalonia, Spain : presentation of the attitudes of the students towards the multilingual education and the multicultural reality of their region / Katerina Stampolaki -- Diversity in language teaching and democratization of education : a critical approach / Marianthi Oikonomakou and Emmanouil Sofos -- Non-verbal communication in wordless comics / Marianna Missiou -- Plurilingualism in linguistically diverse language classrooms : respecting and validating student identity / Angelica Galante -- Factors affecting, and methods to improve, the language development of EAL learners / Kevin Norley -- Conversations within : journal writing as an alternative form of exploration in foreign language pedagogy / Vasilios Zorbas -- Lived experiences among learners of Chinese origin in complementary schools in Spain / Iulia Mancila -- Stories, second language writers and genre awareness / Maria Melissourgou and Katerina Frantzi -- Identity vs. diversity : issues on recognition, "management" and acceptance of diversity / Michalis Damanakis -- Evolution in terms of theoretical conceptualization of translanguaging in applied linguistics : the example of Greek and French language classrooms / Helene Vasilopoulou -- Language diversity in three Italian communities in the UK : heritage languages and code switching / Margherita Di Salvo -- Acquisition of grammatical phenomena in French as a foreign language / Catherine Kiyitsioglou-Vlachou and Zoi Badraka -- Is translanguaging a possibility in a language class? Theoretical issues and applications in an EFL class / Anastasia Gkaintartzi and Roula Tsokalidou -- Virtual museums of music and ballet in foreign language education / Sladana Maric -- Exploring computer-mediated second language oral proficiency testing / Carla Schnitzer-Hall -- Augmented reality-based creation of comics in primary education / George Koutromanos and Alivizos Sofos -- Developing pedagogically meaningful learning objects for foreign language education / Bessie Mitsikopoulou -- Blogging to develop writing skills in a Greek secondary EFL classroom / Melissa Evangelidi -- Computer-based educational program : developing e-learning skills within German language training for specific purposes / Dusan Fedic.
Keywords: Linguistic minorities -- Education; Multilingual education -- Research; Second language acquisition -- Study and teaching